Neuro-ophthalmology and its contribution to headaches: a case-based approach. (September 2010) - Friedman, Deborah I; Frishberg, Benjamin
Many neuro-ophthalmic conditions are associated with head or ocular pain; some are benign and others are potentially life-threatening. Rather than listing and describing numerous conditions, this article presents three cases interfacing neuro-ophthalmology and headache, with a discussion of the differential diagnosis, approach to obtaining the proper diagnosis, and management. The discussions are not intended to be exhaustive, but include conditions encountered in practice that present a diagnostic challenge. The main issues are highlighted for each clinical scenario.